Methanolic Extract of Distemonanthus benthamianus (Caesalpiniaceae) Stem Bark Suppresses Ethanol/Indomethacin-Induced Chronic Gastric Injury in Rats - Vanessa Mba Matah Marte; Gilbert Ateufack; Marius Mbiantcha; Albert Donatien Atsamo; Carine Flore Adjouzem; Stéphanie Flore Djuichou Nguemnang; Eric Gonzal Tsafack; William Yousseu Nana; Yacine Karelle Madjo Kouam; Elvira Ngoufack Azanze (Gastroenterology Research and Practice)
Distemonanthus benthamianus (Caesalpiniaceae) is a plant from the Cameroon pharmacopoeia very widely used in the treatment of many pathologies among which are gastrointestinal disorders. The main purpose of this study was to assess the healing properties of gastric ulcer from the methanolic extract of Distemonanthus benthamianus and its mechanisms of action. The healing properties of gastric ulcers (chronic ulcer model induced by ethanol and indomethacin) were evaluated in vivo in adult male rats, while the mechanisms of action were evaluated in vitro by anti-inflammatory assay (protein denaturation, cyclooxygenase, and lipoxygenase assays) and immunomodulatory assay (ROS production (using technical chemiluminescence), cytokine (TNF-α, IL-1β, IL-6) production (using ELISA), proliferation of T cells (using liquid scintillation counter), and cytotoxicity (using MTT assay)). The methanolic extract of Distemonanthus benthamianus inhibited protein denaturation (75.63%) and the activities of cyclooxygenase (78.92%) and 5-lipoxygenase (81.54%). The extract also significantly (p<0.001) inhibited intracellular and extracellular ROS production and T cell proliferation and reduced significantly (p<0.01, p<0.001) TNF-α, IL-1β, IL-6, and PGE2 production. At all doses (125, 250, and 500 mg/kg), the extract significantly reduces the ulceration index and the area of ulceration and significantly increases the mass of gastric mucus. In addition, the extract significantly decreases the level of MDA, significantly increases the activities of catalase and glutathione, and then improves the hematological parameters in sick animals. Histological micrographs show that in the presence of the extract, there is advanced reepithelialization with recovery of the ulcerated epithelium. Thus, the extract of Distemonanthus benthamianus has healing properties against gastric ulcers which are associated with its anti-inflammatory, immunomodulatory, and antioxidant effects.